2021
DOI: 10.3390/en14248428
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Implementing Climate/Energy Targets of the Europe 2020 Strategy and the Structural Diversity between Old and New Member States

Abstract: The most important goals included in the Europe 2020 Strategy are climate/energy targets, which determine not only the achievement of its other goals but also climate neutrality by 2050. This article aims to assess the efficiency of implementing the climate/energy targets of the Europe 2020 Strategy and to analyse changes over time, taking into consideration the structural diversity between the old (EU 15) and new EU members (EU 13) in the period of 2014–2018. The assessment of changes in the efficiency of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, achieving the best results in the use of renewable energy sources (52%, countries significantly exceed the required target value) is a positive. Guzowska and Kryk [ 58 ] reached similar conclusions in their paper, according to which Sweden’s high position is related to the long-term implementation of a very precise and purposeful environmental policy. Since the 1970s, the country has increased the emphasis on renewable energy sources and gradually reduced the share of fossil fuel use.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, achieving the best results in the use of renewable energy sources (52%, countries significantly exceed the required target value) is a positive. Guzowska and Kryk [ 58 ] reached similar conclusions in their paper, according to which Sweden’s high position is related to the long-term implementation of a very precise and purposeful environmental policy. Since the 1970s, the country has increased the emphasis on renewable energy sources and gradually reduced the share of fossil fuel use.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast to their conclusions, the opposite views can also be encountered. For example, Guzowska and Kryk [ 58 ] state that new member countries Latvia, Malta and Cyprus were most effective in approaching the targets in environmental area in 2018. According to Firoiu et al [ 18 ], it is possible to expect a higher energy import dependency in the case of small but also island states such as Cyprus and Malta.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the regression analysis Liobikienė, G. and Butkus, M. (2017) showed that economic growth and increasing primary energy consumption will contribute to the growth of greenhouse gas emissions in the EU, which may negatively affect the achievement of the targets. Guzowska and Kryk (2021) also indicated the difficulties of some countries to achieve the target (Bel and Joseph, 2018;Duľová Spišáková et al, 2021), as well as in the field of energy (Mikoláš et al, 2015;Bellotti et al, 2019). According to Liobikien and Butkus (2017), the uneven effectiveness of the energy and climate policy of the EU member, which determined different changes in greenhouse gas emissions, primary energy consumption and the share of RES at the level of individual countries, affects the achievement of the set targets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Guzowska and Kryk [29] sought to evaluate the efficiency of the Europe 2020 Strategy climate and energy targets implementation in the period of 2014-2018. The authors performed DEA and analyzed changes over time by grouping countries into the old (15) and new members (13) of the EU.…”
Section: Literature Reviewmentioning
confidence: 99%